Identification of prawn pathogen bacteria Vibrio spp. Using biochemical test and 16S rRNA gene sequence analysis - Siti Rokhaiya, Binti Hj.Biollah (Universiti Malaysia Sarawak, UNIMAS, 2012)
Pathogenic bacteria Vibrio spp. is among the common problem in aquaculture causing infection to human and commercially important species of crustaceans, bivalve and fish. It also causes large economic losses to aquaculture. In Sarawak, most of aquaculture activity involves shrimp aquaculture industry. Up to date there is no proper documentation on pathogen infected shrimp Litopenaeus vannamei cultured in Sarawak. This study is designed to isolate and determine pathogenic bacteria that infected L. vannamei shrimp cultured in Sarawak using biochemical test and 16S rRNA gene sequence analysis. A total of 6 samples of fresh L. vannamei had been collected from Kuching, Sibu and Mukah wet markets and farms subjected to biochemistry, sensitivity to antibiotics and sequencing of the 16S rRNA gene. The samples collected from Kuching were free from pathogenic bacteria, Vibrio spp. However, there was only one sample collected from Mukah namely DM3(Y) had been determined as Vibrio alginolyticus based on biochemical test and antibiotic sensitivity test. The 1500bp and 1000bp 16S rRNA sequence data (accession number JF700503.1 and EF542800.1) supported this result as data match V. alginolyticus.